Esophageal Varices in Pregnancy Secondary to Hepatic Cirrhosis: A Case Report - Royda D, Syerli; Roziana, Roziana; Indirayani, Ima (CoinReads Media Prima, 2025)
Introduction: Pregnancy complicated by liver disease is a rare but clinically challenging condition. Portal hypertension is one such liver disease that may occur in pregnant women, primarily caused by cirrhosis. Esophageal varices, a manifestation of portal hypertension, carry significant maternal and fetal mortality risks. Case Description: We present the case of a 22-year-old woman referred from the Internal Medicine-Gastroenterology Department with a diagnosis of grade IV esophageal varices and grade IV gastric fundal varices. At the initial referral to the Obstetrics and Gynecology clinic, her pregnancy was estimated at 5–6 weeks gestation. Despite the high morbidity and rarity of this case, the patient maintained the pregnancy until 34–35 weeks of gestation. She had a two-year history of esophageal varices, with previous hospitalizations for melena and hematemesis. Fetomaternal ultrasound revealed a singleton fetus in cephalic presentation, consistent with 34–35 weeks of gestation, with suspected intrauterine growth restriction (IUGR). Abdominal ultrasound suggested hepatic cirrhosis, and endoscopic evaluation confirmed grade IV esophageal and gastric fundal varices. Termination of pregnancy was performed via abdominal delivery. Conclusion: Preventing pregnancy complications, accurate diagnosis, and meticulous management that balances maternal and fetal risks are crucial in such cases to improve outcomes.